Domestic violence among young couples and associated factors in south-west of Nigeria (2018)
Domestic violence among young couples in Nigeria was observed to be an event that can happen anywhere but certain factors seem to increase its likelihood, and its adverse effect on psychological, physical and social wellbeing of the couples and their children. This attracted the attention of this study to examine the influence of personality factors, marital stress and hopelessness on domestic violence among young couples in south-west of Nigeria. The study adopted descriptive cross sectional research design and Questionnaires were used to gather data from the selected young couples. Multistage sampling technique was utilized; Simple random sampling technique was used to select two (2) states out of six (6) states in south-west geopolitical zone of Nigeria and purposive sampling technique was used to select two hundred young couples who participated in the study. The result revealed that personality traits had significant joint influence on domestic violence among young couples in south-west of Nigeria (F(5,193)=11.250; p<0.05; R=0.495, R2=0.245) and out the five personality trait (agreeableness, emotional stability, openness to experience, extraversion and conscientiousness) agreeableness, emotional stability and openness to experience had significant independent contribution to domestic violence (b=-0.191; t =-2.795; p<0.05. b=0.270; t = 3.762; p<0.05. b= 0.235; t = 3.476; p<0.05). The result also revealed that there was significant difference in the domestic violence of young couples with low marital stress compared to those with high marital stress (t(198)=-3.121, p<.05). Also, there was significant difference in the domestic violence among young couples with low hopelessness and those with high hopelessness (t(198)=-3.187, p<.05). Furthermore, it was discovered that marital stress and hopelessness had significant joint influence on domestic violence among young couples in south-west of Nigeria (F(2,196)=23.921; p<0.05; R=0.445, R2=0.198). The study concluded with discussion of findings and recommends that young couples with domestic violence should endeavor to seek help from clinical psychologist, mental health practitioners and counseling psychologist in order to help adjust to behaviours that will help keep their marriage from domestic violence before it results to psychopathology